Trends of patient referral to a memory clinic and towards earlier diagnosis from 1985–2009. (1st October 2015) - Grimmer, Timo; Beringer, Stephanie; Kehl, Victoria; Alexopoulos, Panagiotis; Busche, Aurel; Förstl, Hans; Goldhardt, Oliver; Natale, Bianca; Ortner, Marion; Peters, Henning; Riedl, Lina; Roßmeier, Carola; et al.
ABSTRACT: Background: It may be assumed that increased public awareness of dementia due to Alzheimer's disease (AD) together with the availability of efficacious treatment will result in diagnostic evaluation at earlier stages of cognitive decline and diagnosis of dementia due to AD at earlier stages. Methods: All persons that were examined at a university based memory clinic, in Germany, between 1985 and 2009 were included. Results: In the 3, 951 persons identified, linear regression analysis revealed a positive association between Mini Mental State Examination (MMSE) score and year of initial examination (yearIE) ( β = 0.266; p < 0.001). In the 1, 821 patients diagnosed with dementia due to AD, a positive association between MMSE score and yearIE ( β = 0.230; p < 0.001) was revealed. MMSE scores were higher ( β = 0.195; p < 0.001) after the introduction of cholinesterase inhibitors in Germany in 1997. Conclusions: Diagnostic evaluation of individuals occurred at progressively earlier stages of cognitive decline. Dementia due to AD was diagnosed at progressively earlier stages, and this trend was associated with the availability of efficacious treatment. This is the first study on changes in patient referral and diagnosis based on a continuous 25 years period.